Mormor — eller kampen om tiden - Bränström Öhman, Annelie (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2011)
This article, with a title paraphrasing the title of Michael Ende’s well known book Momo, is taking its starting point from the notion of elderly women as marginalized literary characters. However, instead of providing new examples of old facts it is argued that the "antie" (in Swedish: "Tanten") always have followed like a shadow in the footsteps of the Male Hero of, for instance, the crime novel. She has become an alternative representative witness and courier of the insoluble dilemma of time and human existence; she has regained potential to be considered to be the Everywoman of our life narratives. Drawing on famous examples, such as the middle aged Mrs Ramsay and Mrs Dalloway from Virginia Woolf’s novels, but also the article writer’s own grandmother, the article concludes that "Tanten" is a literary figure that must be understood in relation both to (possibly both engre and gender specific) aspects of style and discourse as well as to philosophical questions of time conception.